2004
DOI: 10.1111/j.1468-2338.2004.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Individualism and collectivism revisited: a study of black and minority ethnic women

Abstract: This article seeks to add discussion of the intersection of gender and ethnicity to the debates on individualism and collectivism. In doing so, it challenges the prevailing view, in these debates, of the rise of individualism and the decline in collectivism. Through a study of black and minority ethnic women trade unionists, it shows how a differentiated workforce, rather than leading to individualism at work, may contribute to union renewal and inspire more creative forms of collectivism.The distinction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 36 publications
4
99
0
1
Order By: Relevance
“…Although a study of the civil justice system found that minority ethnic respondents were no more likely to experience workplace problems than white respondents (O'Grady et al, 2005), the URWS found that minority ethnic workers were over-represented in the sample (which, by definition, contained only workers with problems at work) compared with their representation among the low-paid, non-unionized in the labour force. This suggests greater vulnerability to problems and supports evidence that minority ethnic workers are at a greater disadvantage in the labour market as a result of prejudice, racism and xenophobia (Healy et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
“…Although a study of the civil justice system found that minority ethnic respondents were no more likely to experience workplace problems than white respondents (O'Grady et al, 2005), the URWS found that minority ethnic workers were over-represented in the sample (which, by definition, contained only workers with problems at work) compared with their representation among the low-paid, non-unionized in the labour force. This suggests greater vulnerability to problems and supports evidence that minority ethnic workers are at a greater disadvantage in the labour market as a result of prejudice, racism and xenophobia (Healy et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
“…The lack of interface with the insights gained from the gender and Industrial Relations debate is a curious gap in this current wave of research on immigration. Healy et al (2004) do link these debates because of their focus on black women but they are relatively isolated. The gender-related debate implied a very serious critique of the historical packaging of Industrial Relations given its exclusion of women in key parts of the economy yet the immigrant debate until recently seems less concerned with this-perhaps because trade unions themselves are victims of the new employer and employment order but it is more likely to be that the point of emphasis in the debate is seen from the point of the view of the concern with and the question of trade union renewal.…”
Section: Voice Within the Study Of Immigration And Industrial Relatiomentioning
confidence: 97%
“…The study of Healy et al (2004) has focused on the way gender and racially motivated exploitation configures the character of politics and activism within black female workers in the public sector in the United Kingdom, for example. This links with the increasing interest in intersectionality, which focuses on the way different types of inequality combine within different constituencies and give rise to a variable set of needs and politics (Verloo 2006).…”
Section: The New Concern With Voice Representation and The Concept Omentioning
confidence: 99%
“…Returning to the interactionist critique, being active within a certain field can lead to the realization that a person's interests reconcile with others -in short, that the individual's concerns can best be considered as part of a collective organization, such as a trade union (Madsen 1997). For Healy, Bradley and Mukherjee (2004), this reflects a shift towards 'instrumental collective' justifications for joining a union where, although the initial impetus to join may be due to individually directed motives, these are based within, and develop according to, a collectivity. Individualization does not spell the end of trade unions; rather, 'collective orientations are never given, but must be developed, fought for and sustained by individuals' (Healy et al 2004:464).…”
Section: Pre-existing Associationsmentioning
confidence: 99%